Answer:
Solution for 2z-4=12-1z equation:
Simplifying
2z + -4 = 12 + -1z
Reorder the terms:
-4 + 2z = 12 + -1z
Solving
-4 + 2z = 12 + -1z
Solving for variable 'z'.
Move all terms containing z to the left, all other terms to the right.
Add 'z' to each side of the equation.
-4 + 2z + z = 12 + -1z + z
Combine like terms: 2z + z = 3z
-4 + 3z = 12 + -1z + z
Combine like terms: -1z + z = 0
-4 + 3z = 12 + 0
-4 + 3z = 12
Add '4' to each side of the equation.
-4 + 4 + 3z = 12 + 4
Combine like terms: -4 + 4 = 0
0 + 3z = 12 + 4
3z = 12 + 4
Combine like terms: 12 + 4 = 16
3z = 16
Divide each side by '3'.
z = 5.333333333
Simplifying
z = 5.333333333
Explanation: